Preparation and Stability Evaluation of Size‐Controllable PDHCA‐β‐CD Nanoparticles as Drug Carrier. Issue 7 (19th April 2017) - Chu, Hong; Zhao, Xue; Liu, Shirong; Ni, Zhongbin; Shi, Dongjian; Chen, Mingqing
Abstract: A novel biocompatible polymer was prepared by grafting the derivate of β ‐cyclodextrin (6‐SH‐ β ‐CD) onto poly(3, 4‐dihydroxycinnamic acid) (PDHCA) via Michael addition. PDHCA‐ β ‐CD nanoparticles were prepared by the self‐assembly of amphiphilic PDHCA‐ β ‐CD polymer with N, N ‐dimethylformamide (DMF) as good solvent and water as poor solvent. The PDHCA‐ β ‐CD nanoparticles were monodispersed with spherical morphology as shown in the scanning electron microscopic (SEM) images in accord with the result of dynamic light scattering (DLS) measurement. The size of the nanoparticles could be controlled from 60 to 180 nm by tuning the grafting degree (GD) of PDHCA‐ β ‐CD polymer and also significantly influenced by the amount of water used during the process. These as‐prepared nanoparticles were stable without any significant change in the particle size after six‐months' storage and even after being irradiated by UV at λ >280 nm for hours. The formation mechanism of PDHCA‐ β ‐CD nanoparticles was explored. The content of doxorubicin (DOX) loaded onto the nanoparticles was up to 39% with relatively high loading efficiency (approximately 78.8% of initial DOX introduced was loaded). In vitro release studies suggested that DOX released slowly from PDHCA‐ β ‐CD nanoparticles. These features strongly support the potential of developing PDHCA‐ β ‐CD nanoparticles as carriers for the controlled delivery of drug. Abstract :